Molecular beacons for the interrogation of engineered bone systems - Ng, Wei Kai (2017)
Replicating the bone microenvironment of the metastatic niche is a key challenge in bone metastases studies. Although multiple studies have provided outlines for producing a vascularized bone microenvironment, they are not without their limitations. Here we aim to optimize a protocol to generate an accurate bone microenvironment model using endothelial cells and mesenchymal stem cell aggregates (spheroids) within a microfluidic device, and to evaluate the possibility of studying osteogenic gene expression levels within the microenvironment using molecular beacons. We found that the spheroids, when differentiated provides a good representation of osteogenic micro-tissue. We also investigated the factors to generate the bone microenvironment, and have managed to form a micro-vascular network within our microfluidic device. However, additional optimization experiments are required to fully optimize all parameters and obtain perfusable micro-vascular networks consistently. We also evaluated the use of poly-lactic-co-glycolid microparticles to deliver molecular beacons to the cells, and have found out that the uptake of the microparticles are poor. Hence, alternative methods of molecular beacon delivery need to be tested. Our projects shows potential in further development, and if successful, can provide an accurate platform for cancer metastasis studies.